Objective Assessment of Learning Outcomes in Higher Education: Do We Ignore the Issue? - Ljubotina, Damir (2007)
One of the most important goals of the Bologna process is to promote student and professor mobility. This process brings into focus the issue of learning outcomes’ evaluation and standardization, as well as the comparability between different educational systems. There is general acceptance of the value of the learning outcomes approach within the context of the European Higher Education Area (it improves transparency and choices for students and encourage mobility), and its implications for the development of ECTS for the curriculum, assessment, quality assurance, qualifications frameworks and institutional quality culture. What is meant by learning outcomes is the set of competences including knowledge, understanding and skills a student is expected to know/understand/demonstrate after completion of a learning process. Bologna process also proposes a new specific uniform grading system which consists of a 7-point scale. In this paper, we discuss the disadvantages of a normative-referenced approach, which Bologna proposes, and suggest the possible use of the criterion approach to measurement of learning outcomes in higher education. The first goal of the paper was to present the results of the grading system analysis in 61 countries (26 European). A great diversity of national grading scales in different countries was observed. They vary in their discriminativity, as well as in marks for different grades, intervals between grades and meanings of particular grades. The results showed the inexistence of explicitly defined criteria for associating particular grades to particular quality and quantity of students’ learning outcomes. The finding that most of the examined world countries have no defined grading criteria or instructions puts the metric characteristics of students’ grades into question. The inexistence of rules provides space for measurement error and makes the comparison more difficult. The second goal was to develop a set of psychometrically validated instruments whose format of tasks would enable measurement of the different knowledge dimensions, according to revised Bloom’ s taxonomy. It is, within the cognitive domain, one of the most reknowned categorizations which enables goal operationalization. After certain modifications (Anderson, Krathwohl, 2001) it details six levels of learning outcomes within the cognitive domain: recall of information, comprehension, application, analysis, understanding causal relations, judgement/critical thiniking and synthesis or the ability to create new ideas. The authors emphasize the importance of validating psychometric characteristics of learning outcomes tests, especially reliability, validity and discriminativity. Preliminary versions of tests were implemented on a sample of students at the University of Zagreb. Psychometric analysis was conducted. In the context of quantitative test theory metric characteristics and parameters of tasks were assessed. Factor structure, validity, reliability and discriminativity are discussed.